ANALISIS KUANTITATIF DAN STABILITAS -KAROTEN PADA BIOMASSA PASTA DAN SERBUK DARI MIKROALGA Porphyridium cruentum DAN FORMULASINYA PADA EFFERVESCENT - arkham, muhammad nur; agustini, tri winarni; cahyono, bambang (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Porphyridium cruentum was microalgae which has -carotene compound.Supplement drinks was favored by the consumers in the form of effervescent. The purpose ofthis study is the quantity of -carotene compounds in the microalgae P.cruentum in pastesand powders biomass during storage at different temperatures, to know the making ofeffervescent from the formulations for characteristics. The results for quantitative andstability analysis of -carotene from pastes biomass was better in cold storage by observationday-0, the 5 and the 10 are 0.026 ± 0.001, 0.023 ± 0000 g/100g, for powder biomass also incold storage 0.022 ± 0.001, 0.018 ± 0000 g/100g, and 0.015 ± 0.001. The best effervescentformulation added from powder biomass was 4% with the comparison the controls 0%, thetested of water content 6.52% ± 0.20, pH 5.21 ± 0.03, 2.10 minutes dissolved time andhedonic value of testing of appearance 7,2; colour 7,4; aroma 7,3; and flavor 7,4